Relationship Of Knowledge Discuss Between Nurses And Leaders In The Effectiveness Of Implementing Nursing Care - Yuliansari, Pratiwi; Nugroho, Christianto (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aim to examine the relationship of knowledge discuss between nurses and leaders in the effectiveness of implementing nursing care. This type of research is descriptive correlational with cross sectional approach, with sampling by cluster sampling, and obtained a sample of 80 respondents. Research data were collected by questionnaire and observation form by researchers. The results of the study found the significance value of knowledge discuss to effectiveness nursing care is p = 0.002 which can be interpreted that there is a relationship between knowledge discuss to effectiveness nursing care by supervision , with a percentage of the opportunity to influence by 51%. Nursing care is the main service in the hospital that must be maintained quality.